Drag on a slip spherical particle moving in a couple stress fluid - E.A. Ashmawy (Alexandria Engineering Journal, 2016)
The creeping motion of a rigid slip sphere in an unbounded couple stress fluid is investigated. The linear slip boundary condition and the vanishing couple stress condition are applied on the surface of the sphere. A simple formula for the drag force acting on a slip sphere translating in an unbounded couple stress fluid is obtained. Special cases of the deduced drag formula are concluded and compared with analogous results in the literature. The normalized drag force experienced by the fluid on the slip sphere is represented graphically and the effects of slip parameter and viscosity coefficients are discussed.